A new species of Pentaceration (Paramunnidae, Isopoda, Crustacea) from the Otago region of Aotearoa New Zealand - Peart, Rachael A.; Schnabel, Kareen E. (Frontiers in Marine Science, 2024)
A new paramunnid species, Pentaceration forkandbrewer sp. nov., is described from Otago, Aotearoa New Zealand (Otago region). The majority of specimens examined were collected during a 'Ports of Otago' survey carried out by NIWA Christchurch. Pentaceration forkandbrewer sp. nov. can be identified by the following characters: by the lack of dorsal protuberances, the reduced midhead spine and the flattened, and the calcified pereon with serrated margins. All the pereonites end in a point and are reasonably broad. P. forkandbrewer sp. nov. is most similar to the Australian species P. serrata Just, 2011 and the Argentinian species P. pleonarietis Doti, 2017. The new species is described and an adapted key to the Pentaceration species of Aotearoa New Zealand is provided.